Edukasi Jamu Sebagai Upaya Pencegahan Hipertensi dan Diabetes Mellitus di Kutai Barat - Rahayu, Eka Putri; Ningsih, Riyan; Mubarak, Muhammad Ikhsan Al (Yumary: Jurnal Pengabdian kepada Masyarakat, 2025)
Purpose: This community service initiative aimed to promote the use of traditional herbal medicine for treating hypertension and diabetes mellitus among residents of Empas Village, Melak District, West Kutai Regency. The program sought to enhance public awareness of the benefits of herbal medicine as a safer alternative to generic pharmaceuticals. As part of Indonesia’s cultural heritage, herbal medicines offer natural ingredients with minimal side effects that can provide significant health benefits. Methodology/approach: The activity comprised educational sessions focused on herbal medicine recipes for managing hypertension and diabetes. These sessions were conducted at the local posyandu (integrated health post) with 30 community participants present. Results: The survey data revealed a high prevalence of hypertension and diabetes within the village. Through the distribution of informational pamphlets and systematic educational presentations, participants gained an improved understanding of the therapeutic potential of local medicinal plants. Conclusion: Education on the use of traditional herbal medicine has succeeded in increasing public knowledge and awareness regarding the potential of herbal medicine as a viable alternative treatment for hypertension and diabetes mellitus. Limitations: The participants were limited to only Empas villagers with a total of 30 persons. Contribution: This community service positively impacted villagers by promoting the use of medicinal plants, potentially improving their overall quality of life.